2022
DOI: 10.1038/s41398-022-01903-3
|View full text |Cite
|
Sign up to set email alerts
|

Desmosterol and 7-dehydrocholesterol concentrations in post mortem brains of depressed people: The role of trazodone

Abstract: Major depressive disorder (MDD) is a common, disabling, and heterogeneous condition that responds unpredictably to current treatments. We previously showed an association between depressive symptoms and plasma concentrations of two cholesterol precursors, desmosterol and 7-dehydrocholesterol (7DHC). Here, we measured total cholesterol and sterol concentrations with mass spectrometry in postmortem brain samples from depressed and control subjects. Mean (±SEM) desmosterol concentration was 8.9 ± 0.97 ng/mg in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In addition, in the most recent study, Cenik et al. have observed increased 7-DHC in human postmortem brain tissue due to TRZ usage, suggesting that DHCR7 inhibition is an integral part of TRZ action ( 22 ). In follow-up studies on sterol biosynthesis health, we found that multiple CNS-targeting medications are strong inhibitors of post-lanosterol biosynthesis, including (but not limited to) aripiprazole, cariprazine, haloperidol, trazodone, and amiodarone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, in the most recent study, Cenik et al. have observed increased 7-DHC in human postmortem brain tissue due to TRZ usage, suggesting that DHCR7 inhibition is an integral part of TRZ action ( 22 ). In follow-up studies on sterol biosynthesis health, we found that multiple CNS-targeting medications are strong inhibitors of post-lanosterol biosynthesis, including (but not limited to) aripiprazole, cariprazine, haloperidol, trazodone, and amiodarone.…”
Section: Discussionmentioning
confidence: 99%
“…The cross-species translatability of findings is always a concern. This concern is alleviated by the fact that cholesterol biosynthesis across the mammalian species is conserved ( 60 ) and that multiple publications show that ARI and TRZ utilization increases 7-DHC levels in the human plasma ( 31 , 61 ) and brain tissue ( 22 ). In addition, we have shown previously that single drug treatments with ARI and TRZ are strong developmental inhibitors of sterol biosynthesis both in vitro and in vivo, with deleterious consequences on prenatal brain development ( 33 , 34 , 52 , 61 , 62 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We and others have previously documented the strong sterol biosynthesis inhibitory activity of ARI and TRZ on the developing and adult brain, neurons, and astrocytes [ 19 , 20 , 49 , 68 ] across various in vitro and in vivo models. Furthermore, it is apparent that the same 7-DHC elevating effects of TRZ can be also observed in human blood and postmortem brain [ 18 , 19 , 54 , 69 ]. Our current findings raise the possibility that the 7-DHC elevating effects of ARI and TRZ can impact the development of other tissues beyond the CNS.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in rodents have shown that both ARI and TRZ affect brain tissue through unique signaling pathways and their effects are not always directly related to their binding on dopaminergic and serotonergic receptors [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 ]. ARI has been shown to have neuroprotective effects in stroke recovery by promoting dopaminergic survival and neuroprotective effects in a mouse model of Alzheimer’s Disease [ 23 , 24 ].…”
Section: Introductionmentioning
confidence: 99%